Pengaruh Perilaku Overconfidence Dan Herding Terhadap Keputusan Investasi Saham Pada Generasi Z Di Malang - Fahmy Rahma Zafira; Anik Malikah; Abdullah Syakur Novianto (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This study aims to determine the effect of Overconfidence and Herding on stock invesrment decisions among generation Z investors in Malang. The research method used is a quantitative method with data collection techniques through distributing questionnaires. The research sample consisted of 75 respondents who are generation Z and have stock investment experience. Data were analyzed using multiple linear regression analysis. The results showed that Overconfidence behavior has positive effect on stock investment decisions, while Herding behavior has no effect on stock investment decisions. This indicates that the level of confidence of generation Z investors plays a role in investment decision-making, while the tendency to follow other investor sis not a determining factor. This research is expected to contribute to the development of literacy behavior finance and become a consideration for young investors Keywords: Overconfidence, Herding, Investment Decisions, Generation Z